(untitled) (Progressive Agriculture, 2019)
Extreme cyclone events are now occurring more frequently in Bangladesh. Bangladesh experiences severe 52 cyclones from 1960 to 2010 where, the approximate percentage of storm surge impact is 40%, the largest in the world. A severe cyclone in 1970 and 1991 caused loss of 300,000 and 200,000 lives. It is reported that 210000, 36000, and 3500 tonnes of boro rice, aus rice, and other food crops (e.g. potatoes and vegetables) were totally destroyed by 1991 cyclone. The storm surge killed huge livestock and caused loss of 100% of freshwater fish. Recently, the super cyclonic storm SIDR (2007) and AILA (2009) affected 10,000 and 300,000 people, respectively. Apart from these, cyclones NARGIS (2008) and MOHASEN (2013) are also mentionable. The crop production in the coastal regions of Bangladesh is most vulnerable by cyclones while, sea level rise by 2050 will inundate 17.7% of southern coastal areas. Tropical cyclones could become more frequent with more strength under recent climate change conditions. In this research, a new dimension of extreme weather assessment is done combining GCM and GIS technology and using tropospheric instability indices. The thermodynamic environment, vertical instability characteristics of severe cyclones are indispensable to cope with climate change conditions, and for planning, disaster management, and to reduce the risk of food insufficiency. Progressive Agriculture, Vol. 30, Suppl. 1: 33-41, 2019